Alterations of triple network dynamic connectivity and repetitive behaviors after mini-basketball training program in children with autism spectrum disorder - Weike Zhang; Kelong Cai; Xuan Xiong; Lina Zhu; Zhiyuan Sun; Sixin Yang; Wei Cheng; Haiyong Mao; Aiguo Chen (Scientific Reports)
Abstract Physical exercise has been demonstrated to effectively mitigate repetitive behaviors in children with autism spectrum disorder (ASD), but the underlying dynamic brain network mechanisms are poorly understood. The triple network model consists of three brain networks that jointly regulate cognitive and emotional processes and is considered to be the core network underlying the aberrant manifestations of ASD. This study investigated whether a mini-basketball training program (MBTP) could alter repetitive behaviors and the dynamic connectivity of the triple network. 28 male children with ASD were scanned twice with resting-state functional MRI and assessed for repetitive behaviors using the repetitive behavior scale (RBS-R). 15 children in the exercise group participated in a 12-week MBTP, while 13 in the control group maintained their regular routines. The feature of Dynamic independent component analysis (dyn-ICA) is its ability to capture the rate of change in connectivity between brain regions. In this study, it was specifically employed to examine the triple network dynamic connectivity in both groups. Compared to the control group, the exercise group exhibited distinct dynamic connectivity patterns in two networks: Network 1 involved cross-network dynamic connectivity changes within the triple network, and Network 2 pertained to dynamic connectivity alterations within the default mode network. Furthermore, a reduction in the RBS-R Total score was observed in the exercise group, reflecting improvements in self-injurious behavior and restricted behavior. Correlation analysis revealed that the amelioration of repetitive behaviors was associated with enhanced dynamic connectivity in parts of the triple network. These findings suggest that MBTP can improve repetitive behaviors in ASD children and is linked to changes in triple network dynamic connectivity.